PROBLEMATIKA PROSES PENYIDIKAN TPPU KEJAHATAN DALAM PERBANKAN: Problems of the Process of Investigating TPPU Crimes in Banking - Adie Arief Wibawa (Fakultas Hukum, Universitas Trisakti, 2024)
In the mechanism for investigating money laundering crimes originating from banking crimes, legally there are overlapping arrangements, which makes it difficult for police investigators, prosecutors' investigators and financial services authorities to synergize. This study was conducted in order to evaluate judicially the workings and issues surrounding TPPU investigations pertaining to financial offenses. by doing a literature research and applying normative legal techniques. Studies can be conducted at every level, including placement, stacking, and integration, according to research. Depending on the circumstances of the case, investigations may be conducted by any investigative body. First: A corruption case; after that, money was laundered; when it was discovered that a criminal banking act had been committed as the predicate offense, the Financial Services Authority and the Corruption Investigation Commission were enlisted. Second, money laundering gave the authorities and the Financial Services Authority reason to believe that the banking crime originated there. Third, the Financial Services Authority and the police will be the first to investigate if money laundering occurs after illegal banking activities are uncovered.